Transmission Mechanism of Monetary Policy Through Asset Price and Exchange Rate Channel in Indonesia - Kurniawan, Arvin; Dwi Astuti, Rini (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
Many studies have been related to monetary policy transmission toward economic growth targets. However, research on monetary policy transmission by including bond yields as a channel has never been done in Indonesia. Therefore, this study will analyze the effectiveness of monetary policy transmission through bond yields compared to monetary policy transmission through asset price and exchange rate channels. This study uses secondary data obtained from the Central Bureau of Statistics (BPS), the Indonesia Stock Exchange (IDX), the Indonesian Economic and Financial Statistics (SEKI) of Bank Indonesia, and the website investing.com. The analysis technique used in this study is Vector Autoregression (VARs). Based on research results, a relatively effective monetary policy transmission channel is the stock asset price channel. It is because the variables in the channel of stock asset prices only take one month to respond permanently to monetary policy, but the contribution between variables is still low. In the bond yield and exchange rate channel, the response shown is only temporary, and the contribution between variables is still weak, so the two channels are ineffective in transmitting monetary policy with the target of economic growth in Indonesia.